ASEAN+3 Bond Market Guide 2016 : Japan (ASEAN+3 Bond Market Guide 2016 : Japan, 2016)
Cover – Title – Copyright – Contents – Figures and Tables – Tables – 1 Publicly Offered Bonds Outstanding – 2 Issuance of Publicly Offered Bonds – 3 Trading Volume of Publicly Offered Bonds – 4 Liberalization of the Japanese Yen and the Corporate Bond Market – 5 Publicly Offered Corporate Bonds Outstanding – 6 Publicly Offered Corporate Bond Issuance Volumes – 7 Corporate Bond Issuing Entities by Structure – 8 Corporate Bond Holdings by Structure – 9 Coverage of the Three Self-Regulatory Organizations in the Japan Bond Market10 Regulatory Framework Matrix in the Corporate Bond Market in Japan – 11 Comparison of Financial Instruments Exchange Act Terms with Market Practice Terms – 12 Overview of Types of Bonds and Notes Issued in Japan – 13 Japanese Government Bonds Outstanding – 14 Trading Volume of Japanese Government Bonds by Category – 15 Local Government Bonds Outstanding by Type – 16 Government Agency Bonds Outstanding by Type – 17 Corporate Bonds Outstanding by Type – 18 Bank Debentures Outstanding – 19 Nonresident Bonds Outstanding by Type – 20 Commercial Paper Outstanding21 Commercial Paper Outstanding by Issuer – 22 Bonds, Notes, and Commercial Paper Outstanding by Type (JPY trillion) – 23 Bonds, Notes, and Commercial Paper Outstanding by Type (number of issues) – 24 Public Sector Bonds Outstanding by Type (JPY trillion) – 25 Corporate Bonds, Notes, Commercial Paper Outstanding by Type – 26 Methods of Japanese Government Bond Issuance – 27 Sample Wording of the Transfer Restrictions in the Terms and Conditions of Notes – 28 Classification and the Change of Status of Investors in Japan – 29 Change in Number and Value of Securitized Product Issuance Market30 Summary of the Enactment of Securitization-Related Laws – 31 Bond Market Transactions by Type and Party – 32 Bond Lending Balances – 33 Bond Market-Related Derivatives Products on the Osaka Exchange – 34 Standard Underwriting Fee Schedule for a Public Offering of Bonds – 35 Standard Fiscal Agent Fee for a Public Offering of Corporate Bonds – 36 Standard Fee Rates for Applicable Agent Services – 37 Short-Term Corporate Bonds-Participation in the Book-Entry System – 38 Short-Term Corporate Bonds-Book-Entry-Related Fees – 39 Corporate Bonds-Participation in the Book-Entry System40 Corporate Bonds Book-Entry-Related Fees – 41 Other Typical Fees and Costs in the Context of Corporate Bond Issuance – 42 Taxation Treatment for Nonresident Investors (Foreign Juridical Persons) – 43 Taxation Treatment for Resident Japanese Investors – 44 Summary of Taxation System for Financial Products for Japanese Resident Individuals before and after Reform – 45 Japanese Organizations in the Islamic Financial Services Board – 46 Excerpt of Underwriting Examination Items from the Rules and Detailed Rules Concerning Underwriting, Etc. of SecuritiesA1 Group of Thirty Compliance for Japan